Kinerja Kerja Pegawai Ditinjau dari Aspek Kompetensi dan Disiplin Kerja di Dinas Pendidikan Pemuda dan Olahraga Kabupaten Sikka - Cicilia Ayu Wulandari Nuwa; Imelda Virgula Wisang; Yoseph Darius Purnama Rangga; Vinsensius Ama Muda; Viktor Eko Transilvanus (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
The research aims to analyse the influence of competence and work discipline on the work performance of the staff at the Youth and Sports Education office in Sikka district. The study used a sample of 57 employees as respondents. The type of research used is quantitative research. While the method used is sampling saturation. The results showed that multiple linear regression equations in the study were known that Y = 6.306 + 0.076 X1 + 0.696 X2 where competence (X1), did not have a partial effect on employee work performance (Y). Meanwhile, the working discipline partially affects the employee's work performance (Y) and competency variables (X1) and work discipline (X2) simultaneously influence the work performance of the staff (Y) of the Youth and Sports Education Office of Sikka District. Keywords: Competence, Work Discipline, and Employee Work Performance